MEASURING THE EDUCATIONAL EFFICIENCY OF AREA DEVELOPMENT PROGRAMMES OF WORLD VISION GHANA-NORTHERN SECTOR - Sam Napoleon Bellua; Sebil, Charles; Bumbokuri Jude (European Scientific Journal, ESJ, 2013)
Purpose: In this age of knowledge economy, Non-governmental organisations play an important role in the development of a country. As donors expert judicious and effective use of their monies, non-governmental organisations are obviously obliged to put to efficient use of their resources. This study evaluates the relative efficiencies of educational efficiency of the area development programmes of World Vision Ghana-Northern sector in the year 2009.Design/methodology/approach: This study applies Data Envelopment Analysis (DEA) to assess the relative efficiency of the educational area development programmes. The inputs were number of staff and number of vehicles, while the outputs were BECE pass rate and completion rate at JHS level. The potential improvements were computed for inefficient ADP.Findings: Results show that the average efficiency score was 91.6% and that there were three (3) efficient ADPs (Zabzugu ADP, Soboba ADP and Nadowli ADP ) out of the four (4) studied. It was noted that Gushegu ADP would have to reduce its number of staff and number of vehicles to 5 and 2 respectively in order to become efficient.